O geometrach i nawigatorach, czyli dylematy transkultury w życiu literackim współczesnego Quebecu - Jarosz, Krzysztof (Er(r)go. Teoria - Literatura - Kultura, 2008)
Krzysztof Jarosz On Land Surveyors and Navigators: Transcultural Dilemmasin the Literary Life of Contemporary Quebec The text is an introduction to the translation of the essay “Land surveyor and navigator” by Monique LaRue. It discusses specificities of the francophome culture of the Canadian province Quebec since its foundation as New France in 17th century until today, with a particular emphasis on the problems of multiculturality and its Quebec version termed as ‘transculturality.’ The issue of transculturality has become a crucial phenomenon of the 1980s due to the francophone immigrant writers who focused in their work on the problems of their individual and group identity while ignoring identity issues of the native francophone majority. The essay by Monique LaRue, unjustly read by an immigrant feminist Ghila Sroka as a manifestation of xenophobia, had incited in late 1990s a heated discussion which revealed a tension between native Québécois and immigrant population. The text provides a synopsis of the argumentation which formed a fundamental basis of discussion on the transculturality of Quebec in the late 20th century.